2018
DOI: 10.1053/j.jrn.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk of Protein-Energy Wasting Assessed by Subjective Global Assessment in Older Adults With Advanced Chronic Kidney Disease: Results From the EQUAL Study

Abstract: This European multicenter study shows that the prevalence of PEW is high in patients with advanced CKD aged >65 years. The risk of PEW increases substantially with age and is commonly characterized by muscle wasting. Our study suggests that focus on nutrition should start early in the follow-up of older adults with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 47 publications
3
33
0
3
Order By: Relevance
“…For patients on hemodialysis, assessment should be preferably performed before the dialysis session when handgrip strength was shown to be higher than after the dialysis session [169] c Each test is scored in 0 to 4 and the maximum score is 12 [170] [53]. Hence, aging adds up as a contributing factor to the etiology of sarcopenia in CKD.…”
Section: Sarcopenia and Ckdmentioning
confidence: 99%
“…For patients on hemodialysis, assessment should be preferably performed before the dialysis session when handgrip strength was shown to be higher than after the dialysis session [169] c Each test is scored in 0 to 4 and the maximum score is 12 [170] [53]. Hence, aging adds up as a contributing factor to the etiology of sarcopenia in CKD.…”
Section: Sarcopenia and Ckdmentioning
confidence: 99%
“…Elderly patients with CKD were more likely to suffer mortality than to progress to end-stage renal disease (ESRD) due to complications and comorbidities 6,7. They also had a high prevalence of geriatric syndromes, including depression, cognitive impairment and malnutrition 810…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in six European countries, it was reported that among older patients (aged >65 years) with an advanced stage of kidney disease the prevalence of PEW is quite high as assessed by the 7-point SGA rating. Loss of fat tissue and muscle wasting was more common in patients aged more than 80 years 32 . Similarly reported in 2017 Campbell studied that SGA can effectively predict the risk of mortality among dialysis and non-dialysis CKD patients 33. In 2001 Kalantar studied serum albumin level was lower in SGA malnourished patients receiving continuous ambulatory dialysis 34 .…”
Section: Pg-sga In Chronic Kidney Diseasementioning
confidence: 98%